HPLC method for quantifying verbascoside in Stizophyllum perforatum and assessment of verbascoside acute toxicity and antileishmanial activity - Alves, Osvaine Junior Alvarenga; Ozelin, Saulo Duarte; Magalhães, Larissa Fernandes; Candido, Ana Carolina Bolela Bovo; Gimenez, Valéria Maria Melleiro; Silva, Márcio Luís Andrade e; Cunha, Wilson Roberto; Januário, Ana Helena; Tavares, Denise Crispim; Magalhães, Lizandra Guidi; Pauletti, Patricia Mendonça (Frontiers in Plant Science, 2023)
We report the chemical composition of the crude leaf extracts obtained from Stizophyllum perforatum (Cham.) Miers (Bignoniaceae); a simple HPLC-DAD method based on mangiferin as internal standard to quantify verbascoside; and the verbascoside acute oral toxicity and antileishmanial activity. HPLC-HRMS-DAD analyses of the crude ethanol S. perforatum leaf extracts (CE-1 and CE-2) revealed that verbascoside was the major constituent in both extracts. CE-1 was purified, and verbascoside and casticin, among other compounds, were isolated. The developed HPLC-DAD method was validated and met the required standards. Investigation of the CE-2 acute toxicity indicated a lethal dose (LD50) greater than 2,000 mg/kg of body weight. Both CE-1 and CE-2 exhibited antileishmanial activity. The isolated compounds, verbascoside and casticin, also displayed antileishmanial activity with effective concentrations (IC50) of 6.23 and 24.20 µM against promastigote forms and 3.71 and 18.97 µM against amastigote forms of Leishmania amazonensis, respectively, but they were not cytotoxic to J774A.1 macrophages. Scanning electron microscopy of the L. amazonensis promastigotes showed that the parasites became more rounded and that their plasma membrane was altered in the presence of verbascoside. Additionally, transmission electron microscopy demonstrated that vacuoles emerged, lipids accumulated, kinetoplast size increased, and interstitial extravasation occurred in L. amazonensis promastigotes exposed to verbascoside. These findings suggest that S. perforatum is a promising candidate for further in vivo investigations against L. amazonensis.